Oligarchic Politics: Elections and Party-List System in the Philippines - Beltran, Richard Henrick I. (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 1 (2008): Contentious Politics)
Review of Oligarchic Politics: Elections and Party-List System in the Philippines.
Keywords: oligarchy, elections, party-list, Philippines